Diferencia entre sentido y referencia (2012)
This lecture aims to introduce philosophy of language. This issue should be carried out based on the following questioin: What do names mean? Therefore, I do not intend to cover all areas of languages, philosophy but to supply the basic knowledge, specially, Frege's differentiation between sense and meaning. The motive of this approach is the following: specifically, in the example of the theory of names both basic problems and key questions in philosophy of language can be retaken. Consequently, a focus on this issue is offered at the light of an event as an introduction feature. In the remaining issues, there are a few introductory sistematic studies in the development of the theory of the names at the beggining of the modern philosophy of language up to the most recent and newest principles.